PENGARUH PERPUTARAN KAS DAN PEMBERIAN KREDIT PRODUKTIF TERHADAP PROFITABILITAS SERTA DAMPAKNYA TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PT. BPR RAGA SURYA NUANSA PONOROGO) - Dini Nurrahmawati; Titi Rapini; Edi Santoso (ASSET: Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study was to determine the effect of Cash Turnover and Earning Credit on Profitability and Impact on Company Value at PT. BPR RAGA SURYA NUANSA PONOROGO by using Multiple Linear Regression Analysis and Path Analysis techniques as a correlation of cause and effect relationships. Based on the results of the analysis and discussion described, it can be seen that 1). Cash velocity has a positive effect on the profitability of ROE and ROA. 2). Provision of Earning Loans has a positive effect on ROE and ROA profitability. 3). ROE and ROA profitability has a positive effect on Company Value. 4). Cash circulation and lending together have a positive effect on profitability. 5). The Cause and Effect Relationship of Cash Turnover and Earning Credit and Profitability to Company Value has a positive impact on the company.